Mechanism of ZnO refining Mg-3Al alloy: experiment research and first principles calculation - Shuqing Yang; Kang Wei; Qing Sun (Materials Research Express)
ZnO (added in the form of industrial zinc ash) was used as an inoculant to refine the Mg-3Al alloy melt. The effect of ZnO addition amount was studied, and the structure and component characteristics of heterogeneous nucleus were observed using SEM. The refinement mechanism was further analyzed using first principles calculation. The results indicate that Mg-3Al alloy can be effectively refined by ZnO (industrial zinc ash), with the best refinement effect when adding 1 wt%. The SEM observation results show that the particle composition is mainly Mg, Al, Zn, and O. First principles research shows that Mg is stably adsorbed on the T site of ZnO $(000\mathop{1}\limits^{\unicode{773}})$ surface, ZnO plays a refining role in the initial stage of nucleation. The enthalpy calculation results indicate that ZnO reacts during the nucleation process, generating MgAl _2 O _4 and Zn solutes around the particles. MgAl _2 O _4 surface greatly promotes the adsorption growth of Mg atom, MgAl _2 O _4 can effectively refine the alloy.